Diseño de un sistema de generación eléctrica para aprovechar el potencial energético solar como fuente de energía alternativa en el bombeo de agua de riego para la finca Albán, de la parroquia de Tumbaco en el año 2015. - Bucheli Avila, Juan Alberto (2016)
Farms which are far away from public services require, among other things, alternative energies to achieve sustainable production. This research proposes a solution to this problem and the preservation of the environment. Through the design and simulation of a power generation system which allows to use solar radiation for pumping irrigation water in one of the farms, besides supplying electricity to the house. To achieve this goal we determined the levels of solar radiation and the flow of irrigation water, necessary to accomplish the requirements in the different crops produced in the area, analyzing through softwares and modelings the feasibility of implementing these alternative energy systems to benefit rural areas of the country. This research is divided into four chapters. The first chapter is based on the state of the art, where solar radiation is analyzed, as well as irrigation water requirements. In the second chapter the research methodology is developed, where the software to be used is determined. In chapter three we analyze and interpret the results obtained from the different government agencies, to determine the technical parameters and develop the design of a system of power generation, to take advantage of the solar energy potential. The proposal, according to the modeling with the data obtained in the Psim software to determine the photovoltaic solar panels needed for the project, is presented in chapter four, as well as the sizing of the type of electric pump to suction optimum water and provide basic energy to the farm house. These problems are solved by determining the capacity of electricity generation from photovoltaic solar radiation that covers the needs of the Alban farm in the Parish of Tumbaco.